PENGARUH JENIS MINYAK DAN KONSENTRASI LARUTAN ALGINAT TERHADAP KARAKTERISTIK SABUN CAIR CUCI TANGAN - Oktari, Sang Ayu Sri Eka; Wrasiati, Luh Putu; Wartini, Ni Made (JURNAL REKAYASA DAN MANAJEMEN AGROINDUSTRI, 2017)
Percentage used of liquid soap based on the PT. Era Ventura Indonesia from 2014 to 2015 has increased by 8,4% while solid soap by 0,3%. The main components producing soap are oil and base solutions. One component that can be used to improve the soap quality is alginate, which is a natural thickener. The purposes of this research were to know the influence of the type of oil and concentration of alginate solution on the characteristics of liquid handsoap, to find out the best combination type of oil and concentration of alginate solution to obtain liquid handsoap. This research used a factorial randomized block design. The first factor was the type of oil consists of three types, namely: virgin coconut oil, coconut oil and palm oil. The second factor was concentration of alginate solution consist of three levels are : 1%, 2% and 3%. The experiments were grouped into 2 groups to obtain 18 experimental units. The variables observed were viscosity, weight type, high foam, stability foam, water holding capacity, and overall acceptance. The results showed that the interaction between type of oil and concentration of alginate solution had significant effect on viscosity. The type of oil has significant effect on high foam, stability foam, overall acceptance and water holding capacity at 2,3,4 and 5 hours. The type of oil and concentration alginate had no significant effect on the weight type, and water holding capacity at 1 hour. The treatment of palm oil with 1% alginate solution resulted in the best treatment. Keywords: liquid handsoap, type of oil, alginate.